The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.1177/02654075211052247
|View full text |Cite
|
Sign up to set email alerts
|

Romantic relationship dissolution on social networking sites: Self-Presentation and public accounts of breakups on Facebook

Abstract: Social media users post an endless stream of life updates, commentary, and other content. This online self-presentation constitutes a narrative that can be examined as a shared account. In this study, we tested the applicability of Duck’s model of relational dissolution (Duck, 1982; Rollie & Duck, 2006) to participants’ personal and public accounts of their romantic breakups on social networking sites (also referred to as social network sites). We adopted mixed methods (content analysis, survey, and interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…In romantic relationships, greater distress following a breakup is associated with more online monitoring (Fox & Tokunaga, 2015). Recent research on romantic relationships also discusses important signals that can be conveyed via social media following a breakup, including changing profile pictures (Fox et al, 2021). This study also demonstrated a pattern of participants engaging in different types of aggression toward their former partner on social media (e.g., “subtweeting” and sharing songs and media that would be painful for their former partner to hear) or allowing their friends to engage in such aggression on their behalf (Fox et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In romantic relationships, greater distress following a breakup is associated with more online monitoring (Fox & Tokunaga, 2015). Recent research on romantic relationships also discusses important signals that can be conveyed via social media following a breakup, including changing profile pictures (Fox et al, 2021). This study also demonstrated a pattern of participants engaging in different types of aggression toward their former partner on social media (e.g., “subtweeting” and sharing songs and media that would be painful for their former partner to hear) or allowing their friends to engage in such aggression on their behalf (Fox et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Recent research on romantic relationships also discusses important signals that can be conveyed via social media following a breakup, including changing profile pictures (Fox et al, 2021). This study also demonstrated a pattern of participants engaging in different types of aggression toward their former partner on social media (e.g., “subtweeting” and sharing songs and media that would be painful for their former partner to hear) or allowing their friends to engage in such aggression on their behalf (Fox et al, 2021). While this study focused on a sample of adult romantic partners following the breakup of a romantic relationship, similar signals and behaviors may be undertaken by former friends in adolescence, leading to more distress following a friendship breakup.…”
Section: Discussionmentioning
confidence: 99%
“…Decisions about relational curation (i.e., keeping/deleting posted media about the relationship; LeFebvre, Brody, & Blackburn, 2020) and amount of online interaction may also be motivated by desired future romantic or sexual contact (Banas et al, 2021). Indeed, in today’s landscape, a vast majority of contact between ex-partners (interaction such as texting or viewing the other’s social media) and even the process of breaking up might be via technology (Brody et al, 2020; Fox et al, 2021; Koessler et al, 2019; McDaniel et al, 2021).…”
Section: Comprehensive Model Of Pdd (Cmpdd)mentioning
confidence: 99%
“…Three articles are especially centered around theories or theoretical concepts: Sharabi and Hopkins’ (2021) investment model analysis of Instagram posts, Alexopoulos’ (2021) study of infidelity in terms of dissonance, and Fox et al’s (2021) study of breakups. Sharabi and Hopkins’ as well as Alexopoulos’ studies illustrate how well-established viewpoints can be extended to contribute to our understanding of additional phenomena.…”
Section: Final Reflections and A Conclusionmentioning
confidence: 99%
“…Sharabi and Hopkins’ as well as Alexopoulos’ studies illustrate how well-established viewpoints can be extended to contribute to our understanding of additional phenomena. Fox et al (2021), using Facebook posts, survey, and interview data, considered the applicability of Duck’s model of relationship dissolution (Duck, 1982; Rollie & Duck, 2006). The resulting picture is a rich one.…”
Section: Final Reflections and A Conclusionmentioning
confidence: 99%